Heterogeneous computing environment characterization and thermal-aware scheduling strategies to optimize data center power consumption - Al-Qawasmeh, Abdulla, author; Siegel, H. J., advisor; Maciejewski, Anthony A., advisor; Pasricha, Sudeep, committee member; Wang, Haonan, committee member (Colorado State University. Libraries, 2012)
Many computing systems are heterogeneous both in terms of the performance of their machines and in terms of the characteristics and computational complexity of the tasks that execute on them. Furthermore, different tasks are better suited to execute on specific types of machines. Optimally mapping tasks to machines in a heterogeneous system is, in general, an NP-complete problem. In most cases, heuristics are used to find near-optimal mappings. The performance of allocation heuristics can be affected significantly by factors such as task and machine heterogeneities. In this thesis, different measures are identified to be used in quantifying the heterogeneity of HC systems and the correlation between the performance of the heuristics and these measures is shown. The power consumption of data centers has been increasing at a rapid rate over the past few years. Motivated by the need to reduce the power consumption of data centers, many researchers have been investigating methods to increase the energy efficiency in computing at different levels: chip, server, rack, and data center. Many of today's data centers experience physical limitations on the power needed to run the data center. The first problem that is studied in this thesis is maximizing the performance of a data center that is subject to total power consumption and thermal constraints. A power model for a data center that includes power consumed in both Computer Room Air Conditioning (CRAC) units and compute nodes is considered. The approach in this thesis quantifies the performance of the data center as the total reward collected from completing tasks in a workload by their individual deadlines. The second problem that is studied in this research is how to minimize the power consumption in a data center while guaranteeing that the overall performance does not drop below a specified threshold. For both problems, novel optimization techniques for assigning the performance states of compute cores at the data center level to optimize the operation of the data center are developed. The assignment techniques are divided into two stages. The first stage assigns the P-states of cores, the desired number of tasks per unit time allocated to a core, and the outlet CRAC temperatures. The second stage assigns individual tasks as they arrive at the data center to cores so that the actual number of tasks per unit time allocated to a core approaches the desired number set by the first stage.